2011
DOI: 10.1111/j.1447-0349.2010.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Children visiting parents in inpatient psychiatric facilities: Perspectives of parents, carers, and children

Abstract: A significant number of clients utilizing mental health services will also be parents. Being a child of a parent with mental illness increases health risks for the child, and hospitalization of the parent has been identified as one of the most difficult times for children. However, few proactive measures have been taken to understand or provide for the needs of children visiting psychiatric inpatient facilities. The aim of this exploratory study was to identify the perspectives children, their parents, nominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(90 citation statements)
references
References 13 publications
1
89
0
Order By: Relevance
“…O'Brien et al . () also found parents reported self‐stigma in the form of fear of anyone knowing that they were in ‘this kind of hospital’ (mental health unit). Fathers felt ashamed of their hospital admission, and were reluctant to be visited by their children.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…O'Brien et al . () also found parents reported self‐stigma in the form of fear of anyone knowing that they were in ‘this kind of hospital’ (mental health unit). Fathers felt ashamed of their hospital admission, and were reluctant to be visited by their children.…”
Section: Resultsmentioning
confidence: 96%
“…Children identified that leaving their parent following a visit was particularly difficult (O'Brien et al . ). They also expressed concerns regarding getting transport to visit their hospitalized parent, difficulty having their daily needs met due to financial concerns in the family, and the effects of medication on their parent (Maybery et al .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…; O'Brien et al . ). These policies can create a framework that facilitates the parent–child relationship and family connections as part of the recovery plan, by specifying the required skills necessary to implement family‐focused practice (Foster et al .…”
Section: Introductionmentioning
confidence: 97%